ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMP PADA MATERI STATISTIKA - Iasha Nur Afifah khadijah; Rippi Maya; Wahyu Setiawan (IKIP Siliwangi, 2018)
This study aims to describe the mathematical communication skills of junior high school students in Cidaun VIII and examine the errors in completing test questions about statistical materials. The research method used is description method. The study was conducted with the subject of 22 students of SMP class VIII in Cidaun. Problem test given in the form of 5 urain problem. The result of the research shows that the mathematical communication ability as a whole is moderate and there is 1 indicator which is good criteria that is for the indicator to restate the infoermasi using the distribution table appropriately. And there are 4 indicators that enter good criteria that is; the indicator of writing the idea or step of problem solving clearly and appropriately (Good); indicators Present information back using a bar chart and write down the idea or step of problem solving clearly and appropriately (Good); the indicator states or explains the mathematical model of image form into plain language (Good) and the indicator writes what is known and asked using mathematical formula (Good). And can be seen the average score of all questions from all students included into the good criteria that is 69.77%.